Rosacea: Gejala, Diagnosis, dan Tata Laksana: Tinjauan Pustaka - Perdiyana, Angki; Allatib, Arohid; Dhamayanti, Marsita Endy (Cermin Dunia Kedokteran, 2026)
Rosacea is a chronic inflammatory skin condition primarily affecting the central face, characterized by redness, visible blood vessels, and acne-like lesions. The exact cause of rosacea is not fully understood, but it is believed to involve genetic, immune, and environmental factors. The diagnostic criteria for rosacea on the face, particularly the cheeks, nose, and perioral area, include the primary symptom of persistent central facial erythema, often accompanied by flushing in a characteristic pattern that may periodically worsen. Common triggers include sun exposure, stress, and certain foods. The condition is classified into subtypes based on phenotypic presentation, with central erythema as a key symptom. Management requires a multidisciplinary approach, including lifestyle modifications, topical and systemic therapies, and,at times, laser treatments, to improve patient quality of life. The prognosis for rosacea is influenced by two main factors: the severity of the condition and the presence of comorbidities, both of which can affect the patient’s quality of life. Further research is needed to explore the underlying mechanisms and develop more effective treatments.